Flavouring Group Evaluation 51, Revision 2 (FGE.51Rev2): Consideration of alicyclic ketones and secondary alcohols and related esters evaluated by JECFA (59th meeting) structurally related to alicyclic ketones secondary alcohols and related esters in FGE.09Rev6 (2015) - EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) (EFSA Journal, 2016)
Abstract The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) of the European Food Safety Authority was requested to consider evaluations of flavouring substances assessed since 2000 by the Joint FAO/WHO Expert Committee on Food Additives (JECFA), and to decide whether further evaluation is necessary, as laid down in Commission Regulation (EC) No 1565/2000. The substances were evaluated through a stepwise approach that integrates information on structure‐activity relationships, intake from current uses, toxicological threshold of concern, and available data on metabolism and toxicity. The present consideration concerns a group of 24 alicyclic ketones and secondary alcohols and related esters evaluated by JECFA (59th meeting in 2002 and 63rd meeting in 2004). This revision is made due to inclusion of four additional substances cleared for genotoxicity concern compared to the previous version [FL‐no: 07.033, 07.094, 07.112 and 07.140]. The Panel concluded for 23 substances that these do not give rise to safety concerns at the levels of dietary intake, estimated on the basis of the MSDI approach [FL‐no: 02.209, 07.034, 07.035, 07.045, 07.094, 07.095, 07.098, 07.112, 07.126, 07.129, 07.140, 07.148, 07.149, 07.172, 07.179, 07.180, 07.257, 09.027, 09.140, 09.160, 09.230, 09.464 and 09.930]. However, for all substances use levels are needed to calculate the mTAMDIs in order to identify those flavouring substances that need more refined exposure assessment and to finalise the evaluation. Besides the safety assessment of these flavouring substances, the specifications for the materials of commerce have been considered and are adequate for 21 substances. For [FL‐no: 07.094 and 07.112], information on the solubility in water and ethanol is missing. The chemical identity could not be unambiguously confirmed for substance [FL‐no: 07.033]. Therefore the Panel could not consider the JECFA evaluation of this substance and information as to its chemical identity should be submitted.